Paul and the Emergence of Christian Textuality Early Christian Literary Culture in Context. Collected Essays, Volume 1 - Mitchell, Margaret M. (Mohr Siebeck, 2017)
Paulus und die Entstehung christlicher Textualität. Gesammelte Aufsätze, Band 1.
PublicationDate: 20171110
Keywords: New Testament -- ancient christianity -- Tritojesaja -- Paulinism -- Ancient Christianity -- Neues Testament -- Kirchengeschichte -- Array